Glucocorticoid signalling drives reduced versican levels in the fetal mouse lung. (April 2020) - Short, Kelly L; Bird, A Daniel; Seow, Bennet K L; Ng, Judy; McDougall, Annie R A; Wallace, Megan J; Hooper, Stuart B; Cole, Timothy J
Abstract : Glucocorticoid (GC) signaling via the glucocorticoid receptor (GR) is essential for lung maturation in mammals. Previous studies using global or conditional mouse model knockouts of the GR gene have established that GR-mediated signaling in the interstitial mesenchyme of the fetal lung is critical for normal lung development. Screens for downstream GC-targets in conditional mesenchymal GR deficient mouse lung (GRmesKO) identified Versican ( Vcan ), an important extracellular matrix component and cell proliferation regulator, as a potential GR-regulated target. We show that, of the five major VCAN isoforms, the VCAN-V1 isoform containing the GAGβ domain is the predominant VCAN isoform in the fetal mouse lung distal mesenchyme at both E16.5 and E18.5, whereas the GAGα-specific VCAN-V2 isoform was only localized to the smooth muscle surrounding proximal airways. Both Vcan-V1 mRNA and protein levels were strongly overexpressed in the GRmesKO lung at E18.5. Finally, we investigated the GC regulation of the ECM protease ADAMTS 12 and showed that Adamts 12 mRNA levels were markedly reduced at E18.5 in GRmesKO fetal mouse lung and were strongly induced by both cortisol and betamethasone in cultures of primary rat fetal lung fibroblasts. ADAMTS12 protein immunoreactivity was also strongly increased in the distal lung at E18.5, after dexamethasone treatment in utero . In summary, glucocorticoid signaling via GR represses GAGβ domain-containing VCAN isoforms in distal lung mesenchyme in vivo by repressing Vcan gene expression and, in part, by inducing the ECM protease ADAMTS12, thereby contributing to the control of ECM remodelling and lung cell proliferation prior to birth.